Basic Conditions of Validity of Electronic Contracts in Iran and UNCITRAL Model Law - Karimi, Abbas; Akbari, Mohamad (Journal of History Culture and Art Research, 2017)
Diverse activities such as electronic exchange of goods and services, instant digital content delivery, electronic funds transfer, electronic stock exchange, electronic bill of lading, commercial projects, common engineering and design, sourcing, government purchase, direct marketing and post-sales services included in e-commerce field. Due to the increasing spread of the electronic world in all aspects, electronic contracts, in turn, was of great importance and made significant contributions in business contracts. The present study aims to investigate the concept, fundamentals and history of electronic contracts referring to UNCITRAL Model Law on Electronic Commerce and Electronic Commerce Act (1996). The results indicate that in terms of the conclusion and obligations of the parties, contract in cyberspace in general is similar to the contract in the real world and in this respect, there is no major difference between these two contexts. Potential electronic contracts considered as written ones and Electronic signatures recognized as valid as the basis of the validity of the will in electronic trading.